Pengaruh GAAIS terhadap Personal Innovativeness: Sikap pada Lintas Generasi - Kusuma, Vincentia Renata; Kornarius, Yoke Pribadi; Caroline, Angela; Gusti, Triningtyas Elisabeth Putri; Gunawan, Agus (Reviu Akuntansi, Manajemen, dan Bisnis, 2024)
Purpose: To see the attitude of AI towards personal innovativeness and to see the differences in attitudes between generation Z and previous generations Research methodology: Respondents in this study are 1,293 people consisted of entrepreneurs and professional workers covering generation Z and previous generations. Results: GAAIS has influence of 9.5% on personal innovativeness, bus the data showa no statistically significant difference in attitude towards AI between cross-generational. Limitations: The analysis in this study still requires the addition of more in-depth variables such as personality, trust, social and subject norms to be able to predict attitudes towards AI in more depth. Contribution: This study is expected to provide deeper insight into the influence of attitudes towards AI on personal innovativeness, considering that in the future AI will be close on society.